2020
DOI: 10.3389/fmicb.2020.01104
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion From Docosahexaenoic Acid to Eicosapentaenoic Acid in the Marine Bacterium Shewanella livingstonensis Ac10

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which belong to the same class of long chain ω-3 polyunsaturated fatty acids (PUFAs), are present in marine γ-proteobacteria. In contrast to their de novo biosynthesis that has been intensively studied, their metabolic fates remain largely unknown. Detailed information regarding bacterial ω-3 PUFA metabolism would be beneficial for understanding the physiological roles of EPA/DHA as well as the industrial production of EPA, DHA, and other PUFAs. Our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The levels of DHA were influenced by lactation time as well ( Table 6 ), and by dietary factors as nuts ( r = 0.284, p = 0.014) and cereal ( r = 0.318, p = 0.006) intake, but no association between Proteobacteria and these dietary factors was detected. Thus, Proteobacteria could be other factor that influences the levels of DHA in breast milk, as it has been demonstrated that some groups of Proteobacteria can synthetize omega-3 polyunsaturated fatty acids such as EPA (eicosapentaenoic) and DHA [ 70 , 71 ]. The genus Staphylococcus was positively correlated with C18:2 (n-6) 9,12 t ( r = 0.309, p = 0.035) and C18:2 (n-6) 10 t , 12 ( r = 0.301, p = 0.040) isomers [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The levels of DHA were influenced by lactation time as well ( Table 6 ), and by dietary factors as nuts ( r = 0.284, p = 0.014) and cereal ( r = 0.318, p = 0.006) intake, but no association between Proteobacteria and these dietary factors was detected. Thus, Proteobacteria could be other factor that influences the levels of DHA in breast milk, as it has been demonstrated that some groups of Proteobacteria can synthetize omega-3 polyunsaturated fatty acids such as EPA (eicosapentaenoic) and DHA [ 70 , 71 ]. The genus Staphylococcus was positively correlated with C18:2 (n-6) 9,12 t ( r = 0.309, p = 0.035) and C18:2 (n-6) 10 t , 12 ( r = 0.301, p = 0.040) isomers [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…and Colwellia spp. [40,41]. Hence, no study has revealed that gut bacteria can induce EPA production.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial polyunsaturated fatty acid (PUFA) production, including EPA, was previously believed to be limited to marine bacteria, which has been reported in recent years in members of d-proteobacteria retrieved from soil samples. 44 However, to the best of our knowledge, no study has shown that original human bacteria can produce EPA directly. We found that B. bifidum, A. onderdonkii, and Bacteriodes vulgatus did not harbor enzyme genes that drove the EPA biosynthesis in prokaryotes by checking the fecal metagenomic and metatranscriptomic profiles, further suggesting that these bacteria may not be able to produce EPA.…”
Section: Report Llmentioning
confidence: 99%